1968
DOI: 10.1152/ajplegacy.1968.215.2.353
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative studies of blood and bone marrow neutrophils in normal mice

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
105
1
1

Year Published

1978
1978
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(112 citation statements)
references
References 0 publications
5
105
1
1
Order By: Relevance
“…Our results differ from many of these studies in that CS, a natural Gc, was administered in vivo to mice continuously for a period of 3 days, with Gc levels that were consistent with natural models of stress. Another difference between this study and previous studies was the use of mature bone marrow granulocytes for functional analysis instead of blood or peritoneal neutrophils (39,40). Our studies indicated that chemotaxis, phagocytosis, and superoxide production were unaffected or slightly enhanced by in vivo CS treatment.…”
Section: Discussionmentioning
confidence: 58%
“…Our results differ from many of these studies in that CS, a natural Gc, was administered in vivo to mice continuously for a period of 3 days, with Gc levels that were consistent with natural models of stress. Another difference between this study and previous studies was the use of mature bone marrow granulocytes for functional analysis instead of blood or peritoneal neutrophils (39,40). Our studies indicated that chemotaxis, phagocytosis, and superoxide production were unaffected or slightly enhanced by in vivo CS treatment.…”
Section: Discussionmentioning
confidence: 58%
“…Blood drawn from an artery tends to have a lower neutrophil concentration than blood drawn simultaneously from a vein or capillary source. [21][22][23] This difference is likely related to the pulsatile flow of arterial blood, 'pushing' the larger cells away from the rapidly flowing central stream and toward the arterial walls. Because of this, the central stream of arterial blood has a lower concentration of neutrophils.…”
Section: Neutrophil Counts Of Neonates N Schmutz Et Almentioning
confidence: 99%
“…For calculation of the number of ASCs in the total BM, the number of ASCs per million cells was multiplied by the number of cells recovered from both femurs and tibias and by a coefficient of 5.3 (43).…”
Section: Enumeration Of Ascs By Elispotmentioning
confidence: 99%